Case Report: Neuromyelitis Optica After Treatment of Uveal Melanoma With Nivolumab and Ipilimumab - Khimani, Karima; Patel, Sapna P.; Whyte, Andrew; Al-Zubidi, Nagham (Frontiers in Oncology, 2022)
The development of immune checkpoint inhibitors (ICIs), has greatly improved survival of patients with advanced malignancies. ICIs can cause immune-related adverse effects (irAEs) involving any organ. Neurological irAEs are infrequent and have mostly been reported in patients with melanoma. We describe the case of a 57-year-old male with right eye uveal melanoma, gene expression profile (class 2), PRAME (preferentially expressed antigen in melanoma) positive, who received plaque brachytherapy with Iodine-125 for four days with subsequent adjuvant ICIs (immune checkpoint inhibitors), nivolumab and ipilimumab. 18 weeks after discontinuation of immunotherapy, patient presented with acute onset of left-sided headaches, pain with eye movements, and vision loss. Patient was tested positive for serum anti-aquaporin-4 antibody (AQP4-Ab) and was diagnosed with neuromyelitis optica spectrum disorder (NMOSD). Subsequently, he was treated with five days of intravenous methylprednisolone followed by an oral prednisone taper over 10 weeks, with improvement in symptoms. We report a unique case of neuromyelitis optica spectrum disorder (NMOSD) following treatment with ICIs. To our best knowledge this is the third reported case in English literature of NMOSD following ICI therapy and the first reported case of NMOSD caused by ICI treatment in uveal melanoma.